'I know what I am doing': A grounded theory investigation into the activities and occupations of adults living with chronic conditions. (2nd January 2020) - White, Carolynne; Lentin, Primrose; Farnworth, Louise
Abstract: Background: A growing number of adults experience chronic conditions and related disability. However, a limited understanding of the activities and occupations of this population reduces the capacity of occupational therapists to deliver person-centred, occupation-based care. Aims: To investigate the activities and occupations of adults living with chronic conditions. Methods: Sixteen adults with multiple chronic conditions participated in two semi-structured interviews at their home or health center. Grounded theory methods were used to analyze data and construct a conceptual understanding of human occupation. Findings: Human occupation was conceptualized as doing activities and actions with meaning, in the context of one's life, health condition(s), and world. Three, two-dimensional categories of meaning were developed from the data: (i) connecting/reconnecting and disconnecting; (ii) caring and harming; and (iii) contributing and detracting. Conclusions: The findings present a complex, dynamic and multifaceted understanding of the activities and occupations of adults living with chronic conditions. Significance: This study demonstrates the value of exploring the experiences of actual or potential occupational therapy clients to refine the concept of human occupation. An in-depth knowledge of what people do is an essential foundation for person-centred, occupation-based practice.